(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: India stands second for Smartphone usage in the world according to “global market” report. Smartphone addiction affects the younger generations to a greater extent. The objectives of the study was to estimate the proportion of students of age 18–24 years who were addictive to their Smartphone, to estimate the average time spent by them, to find the main reasons for usage and also to find the association between Smartphone usages and sleep quality of the students. Method: A cross sectional community based study was done in Ayapakkam, Thiruvallur district, Tamil Nadu. Two stage cluster sampling methodology was employed for selecting a random sample of 139 students. In the first stage 4 clusters were selected based on the more populous clusters and in the second stage a minimum of 35 students were interviewed from each of the selected cluster. Smartphone Addiction Scale (SAS) and Pittsburgh Sleep Quality Index(PSQI) were the tools used for assessing the association of Smartphone addiction and sleep quality of the students. Data was collected using tablet and Epicollect 5 web application. Descriptive statistics, Chi-Square for association and t-test to determine whether there exists significant difference between the means of two groups was assessed. Results: The proportion of students who were addict to their Smartphone was 52.7% and among them it was more in males (66.2%). On an average 6.42 hours/day was spent on their Smartphone. The major reason behind using their Smartphone was for communication (5.03 hours/day). The association between SAS and PSQI were found to be highly significant (?2 = 11.035, p-value < 0.01). Conclusions: It is an alarming sign that students are prone to addiction to Smartphone. The younger generation must be brought awareness about their Smartphone addiction and heath impact they are prone in due course of time.